Establishment of a multiplex qPCR assay for the detection of pathogens associated with bovine respiratory disease complex - Li, Linghao; Jiang, Qifeng; Li, Siying; Li, Xin; Sun, Shenghe; Wang, Xiyi; Sun, Chuangqi; Jia, Kun; Li, Shoujun (Frontiers in Veterinary Science, 2025)
IntroductionThe bovine respiratory disease complex poses a significant threat to the cattle industry, necessitating a multifaceted approach to address its occurrence. The syndrome is caused by various pathogens such as bovine respiratory syncytial virus (BRSV), bovine parainfluenza virus type 3 (BPIV3), bovine viral diarrhea virus (BVDV), bovine adenovirus type 3 (BAV3), Mycoplasma bovis (Mb), and infectious bovine rhinotracheitis virus (IBRV). The confluence of these pathogens causes substantial economic losses to the cattle industry. Although preventive and control measures have been implemented, containment of bovine respiratory diseases continues to present a formidable challenge, highlighting the need for innovative diagnostic and intervention strategies.MethodsIn this study, we designed specific primers targeting six conserved pathogen genes (N of BRSV, M of BPIV3, 5’UTR of BVDV, Hexon of BAV3, oppF of Mb, and gB of IBRV). Subsequently, we established a multiplexed fluorescent real-time quantitative PCR (qPCR) assay for simultaneous detection of these pathogens.ResultsThe developed method exhibited high specificity and sensitivity, with the lowest detection limits for plasmid DNA standards of BRSV, BPIV3, BVDV, BAV3, Mb, and IBRV being 70.1, 40.4, 15.1, 74.4, 69.6, and 4.99 copies/μL, respectively. The coefficients of variation determined by the assay established in this study were <4%, and the amplification efficiency was 93.84%–111.60%, which showed the reliability and stability of the method.DiscussionThe detection rates for BRSV, BPIV3, BVDV, BAV3, Mb, and IBRV were 7.59% (17/224), 11.61% (26/224), 8.04% (18/224), 22.32% (50/224), 27.23% (61/224), and 8.04% (18/224), respectively. All 224 cows were cases of natural disease. Fifty-six diseased cattle were infected with a mixture of two or more of the six pathogens at a mixed infection rate of 25% (56/224). Therefore, this study successfully developed a highly efficient, rapid, specific, and sensitive multiplex qPCR method to detect major pathogens associated with bovine respiratory diseases. This advancement is expected to significantly influence the future of the cattle industry and serve as a valuable reference for subsequent research in this field.